Enumeration of the Edge Weights of Symmetrically Designed Graphs - Muhammad Javaid; Hafiz Usman Afzal; Ebenezer Bonyah (Journal of Mathematics)
The idea of super a,0-edge-antimagic labeling of graphs had been introduced by Enomoto et al. in the late nineties. This article addresses super a,0-edge-antimagic labeling of a biparametric family of pancyclic graphs. We also present the aforesaid labeling on the disjoint union of graphs comprising upon copies of C4 and different trees. Several problems shall also be addressed in this article.